2014
DOI: 10.14475/kjhpc.2014.17.4.216
|View full text |Cite
|
Sign up to set email alerts
|

Physical Symptoms and Psychiatric, Social, Spiritual and Economical Care Needs of Patients under Home-based Cancer Service

Abstract: Purpose: This study was performed to identify the symptoms and care needs of home-based cancer patients in Korea and to add to the scarce literature on this topic. Methods: Data were collected from patients who subscribed to home-based cancer care services in Jinju. Assessments were performed by nurses at the local public health center. The Edmonton Symptom Assessment System with a numeric rating scale (NRS) was used to identify symptoms, and a four-point Likert scale was used to assess psychological, social, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…A review study by Wang et al, (2014) on the unsatisfied needs of cancer patients showed that these patients have several needs such as physical, financial, social, and spiritual needs (Kang et al, 2014), which is in line with the findings from the present study that include the various aspects of these needs.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A review study by Wang et al, (2014) on the unsatisfied needs of cancer patients showed that these patients have several needs such as physical, financial, social, and spiritual needs (Kang et al, 2014), which is in line with the findings from the present study that include the various aspects of these needs.…”
Section: Discussionsupporting
confidence: 90%
“…In this regard, a review study referred to the unmet physical needs of cancer patients including digestive problems and fatigue (Kotronoulas et al, 2017). A study by Kang et al, (2014) in Korea reported that anorexia is one of the most common symptoms of cancer patients, which was managed by home-based care services (Woo et al, 2015). Kotronoulas et al, (2017) introduced nutritional problems as one of the main needs of cancer patients that receive home care and suggested that providing information about this issue is among the needs of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Service provision teams provided home-visit services for the referred patients and co-managed these services with healthcare home-visit teams when necessary to guarantee quality services for recipients and effectively utilize the resources available at public health centers. Before the project was implemented, patients receiving end-of-life care and were registered at public health centers received intermittent healthcare rather than palliative care from nurses in healthcare home-visit teams [ 11 ]. Specifically, home-based cancer patients registered at public health centers and elderly patients with chronic illnesses registered with healthcare home-visit teams belonged mainly to a highly vulnerable, low-income class and did not receive quality medical services [ 12 ].…”
Section: Discussionmentioning
confidence: 99%